Implementação, validação e aplicação de um modelo de força de lubrificação em simulações CFD-DEM de um leito fluidizado - Campos, João Pedro Ferreira de (Universidade Federal de São Carlos, 2020)
Fluidized bed reactors are commonly used in chemical industry applications, especially in reactions involving heterogeneous catalysis. These equipments have been extensively studied and literature describing its macroscopic dynamic behaviors is largely available. However, the literature regarding the effect of microscopic interactions on these systems is sparse, such as the collisional dynamics of particles immersed in viscous fluids. In this context, the restitution coefficient is an effective way to account for energy dissipation caused by collisions. It is known that the presence of an interstitial viscous fluid when particles collide causes an increase in energy dissipation due to the lubrication force, and thus resulting in a much lower restitution coefficient. The present work aimed to implement a lubrication force model in an open-source CFD-DEM (computational fluid dynamics – discrete elements modelling) code in order to evaluate its effect in fluidized beds. The model was implemented directly into the DEM library and calibrated using experimental data from other works. Once validated, the model was applied in a fluidized bed simulation using viscous liquid and dense particles. The model was in good accordance to experimental data and the fluidized bed simulation results were significantly different when the force was included. It was observed that bed porosity decreased while average particle velocity increased, likely due to an increase in particle agglomeration. Overall the results show that the lubrication force should be taken into account when simulating such systems.
Implementation, validation and application of a lubrication force model in CFD-DEM simulations of a fluidized bed
Keywords: Computational Fluid Dynamics; Fluidodinâmica Computacional; Dense Discrete Phase Model; Método dos Elementos Discretos; Força de lubrificação; Lubrication force; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA